Dynamic changes in modern English discourse - Olga V. Aleksandrova; Elena O. Mendzheritskaya; Victoria L. Malakhova (Peoples' Friendship University of Russia (RUDN University), 2017)
The study looks into the developments in modern linguistic science, its new branches and trends, emphasising the importance of language study on the basis of the unity of all language areas. The authors briefly characterise recent changes in linguistics, paying particular attention to the grammatical system of the English language. The study aims to show the expediency and even necessity of applying the functional approach and the cognitive-discursive paradigm to the study of different linguistic phenomena. The main method used in the study is of functional discourse analysis. Research material is represented by texts of Internet discourse, mobile communication discourse and print media discourse. The study concludes that the use of functional approach in studies of the lexical and grammatical system of the language, and of the cognitive-discursive paradigm in the analysis of discourse helps represent the language in a new dimension, trace new possibilities of human speech activities and new features of the functioning of different levels of linguistic units.